SENSORY QUALITY OF BROWNIES SUBSTITUTED WITH MUNG BEAN FLOUR - Nurul Azizah Choiriyah (Poltekkes Kemenkes Mataram, 2022)
Wheat flour is imported material, so the Indonesian people need to limit the use of this flour. However, brownies are a popular product in Indonesia. Mung bean flour can be used to replace wheat flour in making brownies. This study aims to evaluate the brownie formula using wheat flour and mung bean flour with various concentrations to produce brownies that the panelists prefer. The treatments in this study were the ratio of wheat flour: mung bean flour = 75:0 gram (sample 186), the ratio of wheat flour: mung bean flour = 50:25 gram (sample 318), the ratio of arrowroot flour: banana fruit = 25:50 gram (sample 283). Using mung bean flour with a ratio of mung bean flour: wheat flour = 25:50 produces brownies with sensory characteristics that consumers favor. The use of mung bean flour that exceeds wheat flour can reduce panelists' preferences regarding smell, taste, and overall product. Therefore, using the ratio of mung bean flour: wheat flour = 25:50 is an alternative way to reduce the use of wheat flour in brownie products.